FLYPAPER EFFECT PADA PENGARUH DAU DAN PAD TERHADAP BELANJA DAERAH DI BIDANG KESEHATAN, PENDIDIKAN DAN PELAYANAN UMUM PADA KABUPATEN/KOTA PROVINSI KALIMANTAN BARAT - B01110057, FIANTI LESTARI (Jurnal Pembangunan dan Pemerataan, 2015)
Research about The flypaper effect in general fund allocation and regionally original income to regional expenditure  for health, education and public service on the district or the town in west kalimantan province This study aimed to analyze the effect of the General Allocation Fund (DAU) and Regionally Original Income’s (PAD) to the Regional Expenditure for health, education and public service and to determine whether the flypaper effect occurs in DAU and PAD’s influence to Regional Expenditure for health, education and public service. Object of this study was all of the District/Town in west Kalimantan for the peiode 2009 - 2013. With data compiled from the Region Budget of Revenue and Expense (APBD). The Methodology research used in this research is descriptive quantitative research data used are secondary. The type of data used are secondary data published by Directorate General Of Proportion Finance and other agencies, then the data in processed using Eviews 6 program with panel data regression analysis, random effect model approach. The independent variable are the DAU and the PAD, and the dependent variable is the Regional Expenditure for health, education and public service. As the result of this study show that DAU and PAD have a significant impact on Regional Expenditure for health, education and public service. Through this research indicated that the flypaper effect was not found in DAU and PAD’s influence to Regional Expenditure for health and education,but in orther to Regional Expenditure for public service happened the flypaper effect.   Keywords :  Flypaper effect, General Allocation Fund (DAU), Regionally Original Income (PAD), Regional Expenditure for health, education and public service.